2015
DOI: 10.4028/www.scientific.net/ssp.233-234.51
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Dynamics of the Domain Walls in Multilayer Ferromagnetic Structure

Abstract: The domain walls dynamics and generation and evolution of magnetic inhomogeneities of soliton type, emerging in a thin flat layer with the parameters of the magnetic anisotropy, which are different from other two thick layers of the five-layer ferromagnetic structure, were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
6
0
5
Order By: Relevance
“…Many papers study the effect of spatial modulation of the periodic potential (or the presence of impurities in the system) on the dynamics of the SGE solitons [1,2,5,6,19,28]. The SGE model with impurities describes, for example, a multilayer ferromagnet [40][41][42][43]. The importance of impurity modes in the kink dynamics was shown in [5,28,36].…”
Section: Introductionmentioning
confidence: 99%
“…Many papers study the effect of spatial modulation of the periodic potential (or the presence of impurities in the system) on the dynamics of the SGE solitons [1,2,5,6,19,28]. The SGE model with impurities describes, for example, a multilayer ferromagnet [40][41][42][43]. The importance of impurity modes in the kink dynamics was shown in [5,28,36].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they often took into account the magnetic anisotropy modulation both for the case of point and extended defects [21,33]. It is shown that when a DW passes through a thin magnetic layer with a lower anisotropy value, high-amplitude localized nonlinear waves of magnetization can arise in it [19,33,34]. The amount of energy expended on the excitation of localized waves determine the effective damping of the moving DW and can vary depending on the DW initial velocity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of perturbations, the structure of solitons can be changed and they can be more accurately described by deformable quasiparticles [5]. Soliton's internal degrees of freedom can be excited in this case and they can play a very important role in a number of physical processes [8][9][10][11][12]. Soliton internal modes can be responsible for the non-trivial effects of their interactions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Because, in the considered case, K and W are constant, equations (11,12) give the possibility to find all frequencies ! of the impurity modes in the potential well of given size.…”
mentioning
confidence: 99%